Persepsi Petani Melon Terhadap Perubahan Iklim Di Desa Ganti Kecamatan Praya Timur Kabupaten Lombok Tengah - Suryadi, Arman; Hayati, Hayati; Sjah, Taslim (Universitas Mataram, 2025)
The agricultural sector is the most vulnerable to the impacts of climate change, particularly for horticultural farmers such as melon growers. This study aims to analyze melon farmers’ perceptions of climate change in Ganti Village, East Praya Subdistrict, Central Lombok Regency. A quantitative survey method was applied. The location was selected purposively as Ganti Village is a central melon-producing area. A total of 30 respondents were selected using the snowball sampling technique. Primary data were collected through structured questionnaire-based interviews and analyzed descriptively. The results indicate that farmers have strong perceptions of three key aspects of climate change: changing rainfall patterns, extreme weather events, and their impacts on agriculture. Farmers identified specific indicators of the onset and end of the rainy season as well as heavy rainfall as signs of changing precipitation patterns. Regarding extreme events, they recognized the timing of strong winds, floods, and droughts. Perceived impacts include increased pest and disease incidence, reduced yields and quality, higher crop failure risks, unpredictable water availability, and changes in crop varieties each planting season.